2019
DOI: 10.7717/peerj.7738
|View full text |Cite
|
Sign up to set email alerts
|

Variation of 13C and 15N enrichments in different plant components of labeled winter wheat (Triticum aestivum L.)

Abstract: Information on the homogeneity and distribution of 13carbon (13C) and nitrogen (15N) labeling in winter wheat (Triticum aestivum L.) is limited. We conducted a dual labeling experiment to evaluate the variability of 13C and 15N enrichment in aboveground parts of labeled winter wheat plants. Labeling with 13C and 15N was performed on non-nitrogen fertilized (−N) and nitrogen fertilized (+N, 250 kg N ha−1) plants at the elongation and grain filling stages. Aboveground parts of wheat were destructively sampled at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Studies have shown that there is a possible interaction between grain isotope discrimination in the aboveground dry matter and grain yield; yet studies on this interaction are few, especially during the crop's main growth stages (Liang et al, 2013;Chen et al, 2016;Sun et al, 2019). As a result, further information about N isotope discrimination during N uptake and absorption is needed to effectively track the remobilization of N that had been accumulated during the early crop growth stages and the post-anthesis phase under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that there is a possible interaction between grain isotope discrimination in the aboveground dry matter and grain yield; yet studies on this interaction are few, especially during the crop's main growth stages (Liang et al, 2013;Chen et al, 2016;Sun et al, 2019). As a result, further information about N isotope discrimination during N uptake and absorption is needed to effectively track the remobilization of N that had been accumulated during the early crop growth stages and the post-anthesis phase under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, pulse‐labelled plant materials ( 13 C 15 N‐labelled stalk) were used in this experiment, in which δ 13 C maize stalk is approximately 8% higher than that of the whole maize plant and δ 15 N maize stalk is approximately 5% lower than that of the whole maize plant (Wang, Xu, Pei, et al, 2020; Zheng et al, 2018). Its heterogeneity would cause subtle differences in each treatment throughout the whole cultivation period (Sun et al, 2019). This measured difference between whole maize and stalk δ 13 C and δ 15 N values would amount to a potential overestimate (or underestimate) of <10% for maize stalk incorporation and fate dynamics, as based here on the whole maize 13 C and 15 N values.…”
Section: Discussionmentioning
confidence: 99%
“…In WW, higher exudation for increased nutrient uptake is observed from early growth until owering with a decreasing trend thereafter until full maturity (Sun et al, 2018). At this late developmental stage, C is transported to the head during starch synthesis of the grains (Sun et al, 2019) In light of no Ggt-resistant WW cultivars (Palma-Guerrero et al, 2021), the projected adverse climatic conditions for WW both at European and global scale (Senapati et al, 2021;Zhu et al, 2022) and the premature status of the Ggt-speci c biocontrol research (Osborne et al, 2018;Zhao et al, 2023), there is an urgent need to decipher the mechanisms by which the rotational positions of WW in uences its productivity. Here, we investigated how different rotational positions of WW in uence the allocation of freshly assimilated C in above-and belowground plant parts and its subsequent translocation to the rhizosphere of WW.…”
Section: Introductionmentioning
confidence: 99%